An evaluation on the change of natural areas: the case of Eastern Black Sea settlements - Özkan, Doruk Görkem; Dedeoğlu Özkan, Sinem; Özlü, Seda (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Urbanization has a significant impact on social, economic and environmental sustainability. Dynamic urban development and change processes affect both the natural and built environment. Recently, with the increase in urban population and the expansion of urban areas, the pressure on natural areas has increased. Understanding the relationships between natural and built environmental elements that depend on dynamic processes is important and necessary for the future development and management of urban areas. For this reason, the study aims to analyze land use/land cover changes depending on natural environmental elements in the settlements of the Eastern Black Sea Region for a period of approximately 20 years. Considering the heterogeneous structure of the settlements, a multivariate process was followed at the district level. The data set of the study was provided by CORİNE and Two-Step Clustering Analysis was used as the method. As a result of the study, the changes over time of the districts in similar and different clusters according to their natural environment components were evaluated by comparative discussion. The results will be useful and guiding in providing input to planning decisions regarding the similarities and differences of districts-provinces and sub-regions based on natural environmental components.